Author Correction: Immune regulation by oral tolerance induces alternate activation of macrophages and reduces markers of plaque destabilization in Apobtm2Sgy/Ldlrtm1Her/J mice. Issue 1 (December 2018) - Thota, Lakshmi; Ponnusamy, Thiruvelselvan; Philip, Sheena; Lu, Xinjie; Mundkur, Lakshmi
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper